A comparative study of various mathematical models on swimming critical velocity - Wu, C. F.; Lin, J. C. (2001)
The purposes of this study were to examine the difference between critical power (CP) derived from various mathematical models (V-T nonlinear model, V-1/t linear model, D-T linear model and 3P nonlinear model) and the onset of blood lactate accumulation (OBLA). Subjects were 18 juvenile swimmers. First, each subject swam freestyle for five different distances (25m, 50m, 100m, 200m and 400m) at his/her maximal effort, and the time to complete each distance was recorded for assessing critical velocity by various mathematical models. Next, the subjects swam 400m twice: once at maximal effort, and the other at a constant velocity of 85% of mean velocity of maximal effort. The swimming velocity corresponding to the OBLA was determined by extrapolation. The results were: 1) The coefficient of correlation between the performance of all distances with OBLA and CV was high (0.72~0.99) no matter which mathematical model was used. The longer the swimming distance, the higher the coefficient of correlation was found. 2) Only the 3P nonlinear model produced an estimate of CV that was not significantly different from the OBLA. It is concluded that 3P nonlinear model is the best model to determine swimming critical velocity.